Rapid self-healing, stretchable, moldable, antioxidant and antibacterial tannic acid-cellulose nanofibril composite hydrogels - Ge, Wenjiao; Cao, Shan; Shen, Feng; Wang, Yuyuan; Ren, Junli; Wang, Xiaohui (Carbohydrate polymers, 2019)
•Dynamic cross-linked composite hydrogels were prepared.•Stretchability and mechanical stability of the hydrogels were enhanced by CNF.•Good self-healing property and moldability of the hydrogels were performed.•The hydrogels exhibited antioxidant and antibacterial activities. Here, we designed a self-healing composite hydrogel with antioxidant and antibacterial activities by using cellulose nanofibrils (CNF) and tannic acid (TA) as functional additives. Excellent mechanical stability, moldability, stretchability and rapid self-healing ability without any external intervention were realized in one system due to the combined dynamic borate ester bonding between polyvinyl alcohol-borax (PB) and multi-hydrogen bonding between different components. The rheological measurements indicated the incorporation of CNF and TA to PB system substantially affected the viscoelasticity of hydrogels. The unique antioxidant and antibacterial properties were achieved due to the complexation of TA. These high performance multifunctional hydrogels opens a window for a broad application in the field of smart devices and surface engineering.